MINERAL RESOURCES OF UZBEKISTAN AND THEIR GLOBAL IMPORTANCE - Teshaboyeva Nafisa Zubaydulla qizi,; Baxtiyarova Dilrabo Hikmatillo qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Uzbekistan is one of the richest countries in Central Asia in terms of mineral resources. The nation hosts extensive deposits of gold, uranium, natural gas, oil,  copper,  coal,  phosphorites,  and  various  industrial  minerals  such  as  limestone, marble, granite, and bentonite clay. These resources are critical not only for national economic growth but also for international markets, supporting global industries like energy  production,  metallurgy,  agriculture,  construction,  and  high  technology. Additionally,  the  country’s  rich  ecological  reserves  and  national  parks,  including Chatkal,  Zaamin,  and  Nuratau–Kyzylkum,  contribute  to  sustainable  resource management and environmental protection. This paper examines the geological and economic  significance  of  Uzbekistan’s  mineral  wealth  and  its  growing  strategic importance in the global context.